Relationship between Milker’s Personal Hygiene and Sanitation with Contamination of Escherichia coli in the Fresh Goat Milk of Etawa in Boyong Hargobinangun Village, Pakem, Sleman - Wawan Kurniawan; Dyah Suryani; Wibowo Wibowo (Humanistic Network for Science and Technology (HNST), 2018)
Background: Goat milk of Etawa is one of the fresh milks which contains the perfect nutrition of body need close to be breast milk. The composition is such as carbohydrates, fats, proteins, vitamins and water. Sometimes the important nutrient loses because of contaminated by environmental factors. Other factors that influence the quality of goat milk of Etawa are the udder, feces, water, soil, dust, handling breeder/milker, equipment, and air. The most common of contaminant is bacteria, particularly Escherichia coli. The aim of this study is to determine the association of personal hygiene and sanitation milker with the contamination of Escherichia coli in fresh goat milk Etawa in Boyong Hargobinangun Village Pakem Sleman, Yogyakarta Province. Methods: This was a quantitative cross-sectional study. The sampling method used technique purposive sampling by using inclusion and exclusion criteria. Totally 34 cow milker interviewed and the milk sample tested in laboratory. Results: 15 of 34 milker did not practice good personal hygiene (44.1%); 15 of 34 milker did not have good sanitation. Laboratory test revealed 13 of 34 milk sample contaminated by Escherichia coli (+), and the rest were (-). Result of Chi-square test presented that personal hygiene of milker statistically associated with contamination of Escherichia coli (p-value = 0.049) and sanitation did not associate with contamination of Escherichia coli (p-value = 0.867). Conclusion: Personal hygiene of milker associated to contamination of Escherichia coli in fresh goat milk Etawa in the Boyong Hargobinangun village, Pakem Sleman in 2017. Keywords: Evaluation, POMP for filariasis, Filariasis elimination